Disturbed retinoid metabolism upon loss of rlbp1a impairs cone function and leads to subretinal lipid deposits and photoreceptor degeneration in the zebrafish retina - Domino K Schlegel (eLife Sciences Publications Ltd, 2021)
The RLBP1 gene encodes the 36 kDa cellular retinaldehyde-binding protein, CRALBP, a soluble retinoid carrier, in the visual cycle of the eyes. Mutations in RLBP1 are associated with recessively inherited clinical phenotypes, including Bothnia dystrophy, retinitis pigmentosa, retinitis punctata albescens, fundus albipunctatus, and Newfoundland rod–cone dystrophy. However, the etiology of these retinal disorders is not well understood. Here, we generated homologous zebrafish models to bridge this knowledge gap. Duplication of the rlbp1 gene in zebrafish and cell-specific expression of the paralogs rlbp1a in the retinal pigment epithelium and rlbp1b in Müller glial cells allowed us to create intrinsically cell type-specific knockout fish lines. Using rlbp1a and rlbp1b single and double mutants, we investigated the pathological effects on visual function. Our analyses revealed that rlbp1a was essential for cone photoreceptor function and chromophore metabolism in the fish eyes. rlbp1a-mutant fish displayed reduced chromophore levels and attenuated cone photoreceptor responses to light stimuli. They accumulated 11-cis and all-trans-retinyl esters which displayed as enlarged lipid droplets in the RPE reminiscent of the subretinal yellow-white lesions in patients with RLBP1 mutations. During aging, these fish developed retinal thinning and cone and rod photoreceptor dystrophy. In contrast, rlbp1b mutants did not display impaired vision. The double mutant essentially replicated the phenotype of the rlbp1a single mutant. Together, our study showed that the rlbp1a zebrafish mutant recapitulated many features of human blinding diseases caused by RLBP1 mutations and provided novel insights into the pathways for chromophore regeneration of cone photoreceptors.